Is Conversion from Mycophenolate Mofetil to Enteric-Coated Mycophenolate Sodium Justifiable for Gastrointestinal Quality of Life? - Kyle M. Gardiner; Susan E. Tett; Christine E. Staatz (Adis, Springer Healthcare, 2018)
Abstract Background Globally, enteric-coated mycophenolate sodium (EC-MPS) is replacing mycophenolate mofetil (MMF) in maintenance immunosuppressant regimens. The predominant reason for conversion is the purported improvement in gastrointestinal (GI) quality of life. This paper considers the level of bias associated with studies comparing EC-MPS and MMF for GI-related improvement and provides insight into whether conversion is supported by evidence. Methods Using a pre-determined protocol, a literature search was conducted. Full-text review, data extraction and risk of bias analysis was conducted by two independent authors using the Cochrane domain-based evaluation of risk of bias. The review was reported according to the preferred reporting items for systematic reviews and meta-analyses. Results Twenty-nine studies were included in risk of bias analysis. Of these, only three were deemed a low risk of bias. Across these three studies, there were no statistically significant differences in the proportion of GI-related adverse events nor was there a significant difference in the GI-related quality of life between EC-MPS- and MMF-treated patients in these data. Conclusion There was a high risk of bias across the 29 studies investigating conversion from MMF to EC-MPS for potential improvement in GI-related quality of life. The consolidated results of the three studies with low risk of bias suggest no evidence to convert patients stabilised on MMF. If a patient experiences GI-related adverse events whilst taking MMF, other methods should be explored before conversion to EC-MPS.